2005
DOI: 10.1002/cd.143
|View full text |Cite
|
Sign up to set email alerts
|

Associations of emotion-related regulation with language skills, emotion knowledge, and academic outcomes

Abstract: Research suggests that the development of emotional regulation in early childhood is interrelated with emotional understanding and language skills. Heuristic models are proposed on how these factors influence children's emerging academic motivation and skills.Recently there has been extensive discussion of the construct of emotion-related regulation, including its conceptualization, measurement, and relation to developmental outcomes. Definitions of the construct vary, but in general emotion-related regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
147
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(158 citation statements)
references
References 35 publications
(27 reference statements)
8
147
0
3
Order By: Relevance
“…Because recognition of an expression indudes a cognitive evaluation of the stimulus, identifying an emotion is not sufficient for understanding why the individual rates an expression as having specific intensity in valence or arousal (Lazarus, 1991;Damasio, 1996;Moll, de Oliveira-Souza, Eslinger, Bramati, Mourao-Miranda, Andreiuolo, & Pessoa, 2002;Haidt, 2003;Eisenberg, et al, 2005). The perception and identification of facial expressions are influenced by subjective attribution (Bimler & Paramei, 2006).…”
mentioning
confidence: 99%
“…Because recognition of an expression indudes a cognitive evaluation of the stimulus, identifying an emotion is not sufficient for understanding why the individual rates an expression as having specific intensity in valence or arousal (Lazarus, 1991;Damasio, 1996;Moll, de Oliveira-Souza, Eslinger, Bramati, Mourao-Miranda, Andreiuolo, & Pessoa, 2002;Haidt, 2003;Eisenberg, et al, 2005). The perception and identification of facial expressions are influenced by subjective attribution (Bimler & Paramei, 2006).…”
mentioning
confidence: 99%
“…The research of Eisenberg et al which focused on children language indicated that language greatly affects the emotional development of children, and these emotions also affect academic motivation and their language skills [11]. Instead, it is exciting to observe the research of Marsh at 7.802 students in Hong Kong, which argued that the language of instruction not affect academic self-concept and academic achievements of the students.…”
Section: B Discussionmentioning
confidence: 99%
“…The study about language as the perception of emotion [10]. Furthermore, the research about the association of emotion with language, knowledge, and academic outcome [11], [12]. Research about the relation of language and emotion to children reticence [13].…”
Section: Introductionmentioning
confidence: 99%
“…According to Eisenberg, Sadovsky, and Spinrad (2005), language can directly affect social competence and emotion understanding, which in turn affects emotion regulation abilities. Language can also indirectly affect social competence through emotion regulation abilities.…”
Section: Theoretical Backgroundsmentioning
confidence: 99%